One-year follow-up of continuous aspiration mechanical thrombectomy for the management of intermediate-high and high-risk pulmonary embolism: what is the line between utility and futility?. (14th October 2021) - Pereira, A R; Cale, R; Ferreira, F; Alegria, S; Morgado, G; Martins, A C; Ferreira, M; Gomes, A; Judas, T; Gonzalez, F; Lohmann, C; Repolho, D; et al.
Abstract: Introduction: Percutaneous catheter-directed treatments have emerged at the last decade for the management of acute high- or intermediate-high-risk pulmonary embolism (PE). Good short-term efficacy and safety have been published, but there are limited data regarding medium- to long-term outcomes. Purpose: This study aimed to evaluate 1-year all-cause mortality of acute high- and intermediate-high-risk PE patients (pts) treated with continuous aspiration mechanical thrombectomy. Methods: Twenty-nine consecutive pts with acute central PE (mean age 67.2±14.4 years; 72.4% female; 24.1% active cancer; Charlson comorbidity index 4.5±2.1; 82.8% in class>III of original PESI score; 44.8% high-risk PE) were treated with the Indigo Mechanical Thrombectomy System (Penumbra, Inc) between 03/2018 and 03/2020. Clinical success was defined as improvement in hemodynamic and/or oxygenation parameters or pulmonary hypertension or right heart strain at 48 hours after intervention plus survival to hospital discharge. Data regarding severe adverse events potentially related to the procedure, in-hospital and 1-year all-cause mortality were collected. Results: Clinical success was 75.9%, with a significant improvement in mean paO2/fiO2 ratio (+77.1±103.2; p<0.01), shock index (−0.4±0.4, p<0.01), need for aminergic support (−75.0%, p<0.01), right ventricular function (66.6%, p<0.01) and systolic pulmonary arterial pressure (−10.2±11.5mmHg, p<0.01) at 48 hours after procedure. In-hospital survival rate was 82.8% but severe adverse events potentially related to the procedure occurred in 3 pts (10.3%). One-year follow-up was completed in 93.1% of cases and all-cause mortality rate was 34.5% (n=10 of which half occurred during the index hospital stay). Higher scores of Charlson comorbidity index (5.8±1.9 vs 3.7±1.9, p=0.01) and de novo atrial fibrillation at admission (40% vs 0%, p<0.01) were associated with higher 1-year all-cause mortality occurrence and were identified as 2 independent risk predictors by multivariate Cox regression. Kaplan-Meier curves confirmed its significant influence in 1-year survival free of adverse event (Figure). Time among diagnosis and percutaneous treatment (p=0.99), PESI score (p=0.24) and other clinical, haemodynamic and echocardiographic features did not influence mortality and suggest similarity of the PE severity at baseline. Technical characteristics were also not associated with mortality. Conclusions: Aspiration thrombectomy for acute high- and intermediate-high-risk PE was feasible with a high clinical success rate. One-year all-cause mortality rate was elevated and predicted by high comorbidity index and de novo atrial fibrillation at admission. This data support the national expansion of this new PE treatment, but probably and as similar to other invasive techniques, we need to take into account comorbidities and avoid futility in multimorbidity pts. FUNDunding Acknowledgement: Type of funding sources: None.